THE ROLE OF EDUCATIONAL PHILOSOPHY IN THE FORMATION OF RELIGIOUS AND SOCIAL NORMS ON THE MORAL OF PRIMARY SCHOOL STUDENTS - Irwan Suhendra; Riska Nanda Putri; Yanti Fitria; Yeni Erita (Jurnal Tunas Pendidikan, 2026)
Educational philosophy is the result of deep thought and reflection on education. So education cannot be separated from the morals of students. Moral education is development in the formation of religious and social norms. This research aims to determine the role of educational philosophy in the formation of religious and social norms on the morals of elementary school students. Using several literature sources, totaling 15 articles. This research uses the SLR (systematic literature review) technique, literature sources were obtained from the Google Scholar database in 2018-2023. This research has the final result that educational philosophy plays a role in the formation of religious and social norms regarding morals.